(untitled) (MMIT Proceedings, 2026)
This paper analyzes the mathematical model of a machine vision system and image processing algorithms. The study examines the main components of a machine vision system, including the camera projection model, image filtering methods, segmentation, and object parameter detection. The obtained results show that machine vision systems make it possible to determine the geometric coordinates of objects with high accuracy. The research results can be applied in industrial automation systems, robotics, and agricultural product sorting processes